2010
DOI: 10.1007/s12393-010-9013-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Modified Atmosphere Packaging and Natural Compounds for Food Preservation

Abstract: Spoilage of food products is due to activity of microorganisms or biochemical and physical changes. Various food preservation methods have been developed over the years. Traditionally, chemicals are used to control the activity of microorganisms. An increased awareness by the environmental and health agencies and consumers of the harmful chemical residues in food and environment led to a restricted use of chemical preservatives. This trend, known as green consumerism, has resulted, since the beginning of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 76 publications
1
49
0
1
Order By: Relevance
“…Regarding thyme and oregano essential oils, their antimicrobial activity is due to the high amount of carvacrol and thymol in their composition [42,43]. Other studies conducted in different fruits and vegetables also demonstrated the effectiveness of the constituents of different essential oils (eugenol, thymol, menthol or eucalyptol) to improve the organoleptic quality of food as well as to reduce the microbial growth, by using also a modified atmosphere [8].…”
Section: Study Of the Effectiveness Of The Active Films To Preserve Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding thyme and oregano essential oils, their antimicrobial activity is due to the high amount of carvacrol and thymol in their composition [42,43]. Other studies conducted in different fruits and vegetables also demonstrated the effectiveness of the constituents of different essential oils (eugenol, thymol, menthol or eucalyptol) to improve the organoleptic quality of food as well as to reduce the microbial growth, by using also a modified atmosphere [8].…”
Section: Study Of the Effectiveness Of The Active Films To Preserve Pmentioning
confidence: 99%
“…Many different active agents can be incorporated into the packaging material to improve its functionality. The migration of the active compound may be achieved by direct contact between food and the packaging material or through gas phase diffusion from the inner packaging layer to the food surface [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Modern methods of conservation that can be used in production of food with a low processing level comprise ultrasounds, high-pressure techniques, radiation treatment, pulsed electric field techniques, and modified atmosphere packaging (18). For many years, investigations have been performed to assess the application of specific enzymes in animal production which to eliminate the toxicity of trichothecenes, zearalenone, and ochratoxin by changing the spatial structure of the toxins, as well as their use as bioactive compounds added to feed.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of AITC is higher in the gas phase than in the liquid phase (Shin et al 2010). In this regard, recently some authors have reported the effectiveness of AITC vapour as a preservative in several food, including fish products, as an alternative to common package techniques (Winther & Nielsen 2006;Mastromatteo et al 2010;Pang et al 2013;Giarratana et al 2015). Microorganisms are the major cause of spoilage in seafood products.…”
mentioning
confidence: 99%